2022
DOI: 10.1002/14651858.cd013515.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Psychological therapies for temporomandibular disorders (TMDs)

Abstract: Psychological therapies for temporomandibular disorders (TMDs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 110 publications
0
22
0
Order By: Relevance
“…In order to manage TMD, it is important to reduce stress. 26,27 This can include relaxation techniques, such as deep breathing, yoga and meditation. 26 It is also important to avoid activities that may cause further strain on the TMJ, such as chewing gum, nail-biting and clenching or grinding of the teeth.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to manage TMD, it is important to reduce stress. 26,27 This can include relaxation techniques, such as deep breathing, yoga and meditation. 26 It is also important to avoid activities that may cause further strain on the TMJ, such as chewing gum, nail-biting and clenching or grinding of the teeth.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 This can include relaxation techniques, such as deep breathing, yoga and meditation. 26 It is also important to avoid activities that may cause further strain on the TMJ, such as chewing gum, nail-biting and clenching or grinding of the teeth. 28 Treatment for TMD may include medications, physical therapy or even surgery.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In daily clinical practice, it can be observed that TMD treatment is usually carried out by a team using several types of interventions, including splint therapy [10], physiotherapeutic techniques such as transcutaneous electrical nerve stimulation (TENS) [11], lasers [12], soft tissue therapies [13], joint mobilization and therapeutic exercise (TE) [14] and psychotherapy [15]. As a conservative treatment, PT is increasingly recognized as an essential part of multimodal approach in TMD management.…”
Section: Introductionmentioning
confidence: 99%